Genetic Variability in Plus Tree Families of Bauhinia variegata Linn. For Morphological and Biomass Traits - Anand, R. K.; Chauhan, K. C.; Huse, S. A. (Indian Journal of Agroforestry, 2020)
Bauhinia variegata is an important fodder tree species especially in hills. The seeds were collected from forty eight plus trees selected from different places of Himachal Pradesh and half-sib progeny was raised in nursery of Dr. Y.S. Parmar University of Horticulture and Forestry, Solan, in Randomized Complete Block Design. Data were recorded on morphological parameters and biomass of seedlings. Variance component, heritability and genetic gain were calculated. Highly significant differences were observed for all these traits. Maximum variation was observed for leaf area and minimum for collar diameter. Dry shoot weight depicted highest heritability. Family heritability was higher than individual tree heritability. The genetic gain was found maximum for leaf area and minimum for number of branches per seedling.